Analysis of Village Government Financial Management in Supporting Disaster Emergency Management in High-Risk Villages in North Lombok Regency - Nanang Turmuzi; Yusron Saadi; Moh. Taqiuddin (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2026)
This study aims to analyze village government financial management in supporting disaster emergency response in high-risk villages in North Lombok Regency. North Lombok Regency is one of the regions in West Nusa Tenggara with the highest level of disaster risk, especially after the 2018 earthquake. In these conditions, village governments are at the forefront of responding to emergency situations. However, village financial management is often not adaptive to emergency conditions. This study uses a descriptive qualitative approach with a case study method in two high-risk villages, namely Akar-Akar Village and Bentek Village. The results show that the budget realization of Sector 5 (Disaster Management, Emergency Situations, and Urgent Villages) reached 98–100% in Akar-Akar Village and 76–100% in Bentek Village during the 2022–2024 period. This achievement demonstrates a commitment to managing village funds responsive to emergencies. However, there are still obstacles in the regulatory aspects and the capacity of village officials. This study recommends the need for affirmative policies in the form of technical guidelines for the use of village funds for emergencies that are more flexible and responsive.